2017
DOI: 10.2337/dc16-1774
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trypsinogen Levels in Type 1 Diabetes

Abstract: OBJECTIVEThe pancreas in type 1 diabetes exhibits decreased size (weight/volume) and abnormal exocrine morphology. Serum trypsinogen levels are an established marker of pancreatic exocrine function. As such, we hypothesized that trypsinogen levels may be reduced in patients with pre–type 1 diabetes and type 1 diabetes compared with healthy control subjects.RESEARCH DESIGN AND METHODSSerum trypsinogen levels were determined in 100 persons with type 1 diabetes (72 new-onset, 28 established), 99 autoantibody-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 26 publications
(29 reference statements)
6
42
1
Order By: Relevance
“…Recent studies indicate that there may be autoimmune infiltration of the exocrine portion of the pancreas, and AABs to exocrine proteins have been reported in patients with type 1 diabetes (20,31,41). Exocrine dysfunction has been reported and indicated by reduction in trypsinogen levels in patients with type 1 diabetes and AAB + multiple subjects without diabetes (42). While our study was not powered to make formal comparisons across groups, we observed a trend of lower trypsinogen levels in AAB + multiple subjects and in patients with recent-onset type 1 diabetes, which highlights subclinical exocrine dysfunction in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 50%
“…Recent studies indicate that there may be autoimmune infiltration of the exocrine portion of the pancreas, and AABs to exocrine proteins have been reported in patients with type 1 diabetes (20,31,41). Exocrine dysfunction has been reported and indicated by reduction in trypsinogen levels in patients with type 1 diabetes and AAB + multiple subjects without diabetes (42). While our study was not powered to make formal comparisons across groups, we observed a trend of lower trypsinogen levels in AAB + multiple subjects and in patients with recent-onset type 1 diabetes, which highlights subclinical exocrine dysfunction in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 50%
“…similarly observed abundant CD45‐positive cells infiltrating the exocrine pancreases of non‐diabetic patients who tested positive for islet autoantibody, showing that subclinical pancreatic inflammation begins long before the acute‐onset type 1 diabetes onset. A recent report by Li et al . showed that serum trypsinogen levels are significantly lower in non‐diabetic patients testing double positive for islet autoantibodies compared with seronegative non‐diabetic controls.…”
Section: Discussionmentioning
confidence: 98%
“…20,21 ). Type 1 diabetes patients show a significant reduction in pancreas weight or volume at the time of disease onset, and exocrine insufficiency has been reported [25][26][27][28][29] . Other findings include immunological alterations such as increased incidence of exocrine-specific autoantibodies 30,31 , infiltration of immune cells in exocrine tissue 19,32 , and complement activation localized to vessels and ducts throughout the exocrine tissue 33 .…”
Section: Human Islet Nanotomymentioning
confidence: 99%